Pengaruh Kepuasan Pelatihan Dan Pemberdayaan Psikologis Terhadap Keinginan Berpindah Dengan Keterlibatan Kerja Sebagai Faktor Mediasi (Studi Kasus Pada Karyawan PT. Indo Metro Surya Andola) - Fuadi, Selamet; Nasikah, Durotun; Safitri, Mutia (Jurnal Manajemen DIVERSIFIKASI, 2023)
The research was motivated by the high turnover rate of employees in companies. The aim ofthis research is to determine the effect of training satisfaction and psychologicalempowerment on turnover intention with work involvement as a mediating factor. Thisresearch is quantitative research. With this type of explanatory survey research, the samplingtechnique was nonprobability sampling, as many as 73 employees from PT. Indo Metro SuryaAndola. As a measuring tool, an 80-item questionnaire was used with Likert scalemeasurements and analyzed using Path Analysis. The research results show that trainingsatisfaction has a negative effect on employee turnover intentions. Psychologicalempowerment has a negative effect on employee turnover intentions. Training satisfaction hasa positive effect on employee turnover intentions. Psychological empowerment has a positiveeffect on employee turnover intentions. Training satisfaction has a negative effect onemployee turnover intention, mediated by employee work engagement. Psychologicalempowerment has a negative effect on employee turnover intention, mediated by employeework engagement.